2019
DOI: 10.3390/met9030342
|View full text |Cite
|
Sign up to set email alerts
|

Creep-Ductility of High Temperature Steels: A Review

Abstract: A number of measures of the creep-ductility of high temperature steels are reviewed with an ultimate focus on intrinsic creep-ductility. It is assumed that there will be a future requirement for the determination of long duration creep ductility values for design and product standards in the same way as there is currently for creep strength values. The determination of such information will require specialist modelling techniques to be applied to the complex nature of multi-temperature, multi-heat (multi-cast)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Holdsworth used Eq. ( 9) to draw a schematic trending curve [20], as shown in Figure 2, and divided the curve into three regimes: Regime I was plastic hole growth leading to ductile dimpled failure; Regime II was diffusion-controlled cavity growth and creep ductility decreases with reducing strain rate, whereas in regime III cavity growth was constrained and creep ductility is independent of creep strain rate. It has been commonly observed that low creep ductility is often associated with intergranular fracture and high creep ductility is associated with transgranular fracture.…”
Section: Creep Ductility and Fracture Modementioning
confidence: 99%
“…Holdsworth used Eq. ( 9) to draw a schematic trending curve [20], as shown in Figure 2, and divided the curve into three regimes: Regime I was plastic hole growth leading to ductile dimpled failure; Regime II was diffusion-controlled cavity growth and creep ductility decreases with reducing strain rate, whereas in regime III cavity growth was constrained and creep ductility is independent of creep strain rate. It has been commonly observed that low creep ductility is often associated with intergranular fracture and high creep ductility is associated with transgranular fracture.…”
Section: Creep Ductility and Fracture Modementioning
confidence: 99%
“…The creep ductility of steels, related to the strain that can be accumulated at material rupture, is the topic of a review paper by Holdsworth [6]. A set of features involving creep ductility of high-temperature steels, including acritical analysis of creep ductility data, can be applied to predict long-term ductility exhaustion in multi-temperature and multi-cast data sets.…”
Section: Creep Deformation Damage and Ductilitymentioning
confidence: 99%
“…Despite the use of ZnO nanoparticles as nanofillers, ZnO nanowires (NWs) have also been used to enhance the structural and mechanical properties of polymer composites [ 22 , 23 , 24 , 25 ]. For example, it has been demonstrated that vertically aligned ZnO NWs on the surface of carbon fiber led to a 113% increase in the interfacial shear strength of fiber-reinforced polymer composites [ 22 ].…”
Section: Introductionmentioning
confidence: 99%